2021
DOI: 10.3390/land10121384
|View full text |Cite
|
Sign up to set email alerts
|

Crop Intensity Mapping Using Dynamic Time Warping and Machine Learning from Multi-Temporal PlanetScope Data

Abstract: Crop intensity information describes the productivity and the sustainability of agricultural land. This information can be used to determine which agricultural lands should be prioritized for intensification or protection. Time-series data from remote sensing can be used to derive the crop intensity information; however, this application is limited when using medium to coarse resolution data. This study aims to use 3.7 m-PlanetScope™ Dove constellation data, which provides daily observations, to map crop inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…There are ways to correct for these inconsistencies. For example, Rafif et al [51] used histogram matching (with R [52] packages "raster" [53] and "RStoolbox" [54]) to correct for varying radiometric ranges across PlanetScope images. Images can also be radiometrically corrected through a linear shift from comparison with Landsat or Sentinel data, with the Multivariate Alteration Detection (MAD), or the Cubesat Enabled Spatio-Temporal Enhancement Method (CESTEM) [49].…”
Section: B Planetscopementioning
confidence: 99%
See 1 more Smart Citation
“…There are ways to correct for these inconsistencies. For example, Rafif et al [51] used histogram matching (with R [52] packages "raster" [53] and "RStoolbox" [54]) to correct for varying radiometric ranges across PlanetScope images. Images can also be radiometrically corrected through a linear shift from comparison with Landsat or Sentinel data, with the Multivariate Alteration Detection (MAD), or the Cubesat Enabled Spatio-Temporal Enhancement Method (CESTEM) [49].…”
Section: B Planetscopementioning
confidence: 99%
“…The high temporal resolution of PlanetScope data also allowed for monitoring of algal bloom events and small changes in water quality [55]. In addition, PlanetScope images have been used for several agricultural applications, including monitoring crop growth, management, health, and productivity [48], [50], [51], [56]- [62].…”
Section: B Planetscopementioning
confidence: 99%
“…A study has been carried out to compare PlanetScope dataset with Sentinel-2 dataset by (Mudereri et al 2019) for mapping Striga weed in Kenya and results shows that PlanetScope dataset is more accurate in mapping as compared to Sentinel-2 dataset. Further, PlanetScope dataset has a great potential for producing the crops intensity maps at detailed resolutions (Rafif et al 2021). The study used the 4 band data for mapping four different types of crop classes and found that NIR band to be most extensive for analysing and evaluating the cropping intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Croplands mapping and monitoring is a widely used application of remote sensing given its evident advantages of spatial coverage, cost effectiveness, monitoring ability for its revisiting frequency, and its ability to detect crops stress [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Crop intensity mapping, on the other hand, provides important information on the changes in and productivity of agricultural land [ 14 ]. Specifically, crop intensity mapping refers to the segmentation of agricultural land according to the number of crop planting cycles it exhibits, with cycle numbers ranging from 0 to 3, where 0 refers to no crops occurring, and 3 refers to the case in which the same land experienced 3 complete growth cycles of its crops in one year [ 15 ], [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, crop intensity mapping refers to the segmentation of agricultural land according to the number of crop planting cycles it exhibits, with cycle numbers ranging from 0 to 3, where 0 refers to no crops occurring, and 3 refers to the case in which the same land experienced 3 complete growth cycles of its crops in one year [ 15 ], [ 16 ]. Such a task plays an important role in improving food production, and agricultural planning, through surveying cropland changes [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%